Large-scale slab dynamics as drivers of seismicity: Modeling earthquakes in the izu-bonin-mariana subduction zones - Yida Li; Neil M. Ribe; Zhe Jia (Earth and Planetary Science Letters, 2026)

Carob (Ceratonia siliqua L.) flour as a functional ingredient in fresh wheat pasta: Effect on its technological and sensory properties, oral processing and in vitro health benefits - Susana Ribes; Héctor Gómez-Llorente; Laura Córdoba; Isabel Fernández-Segovia; Ana Albors; José M. Barat; Édgar Pérez-Esteve (Food Research International, 2025)

The removal of dissolved organic matter by marine sponges is a function of its composition and concentration: An in situ seasonal study of four Mediterranean species - M. Ribes; G. Yahel; C. Romera-Castillo; R. Mallenco; T.M. Morganti; R. Coma (Science of The Total Environment, 2023)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Trophic niche separation that facilitates co‐existence of high and low microbial abundance sponges is revealed by in situ study of carbon and nitrogen fluxes - T. Morganti; R. Coma; G. Yahel; M. Ribes (Limnology and Oceanography, 2020)

Polyphase tectono-magmatic evolution during mantle exhumation in an ultra-distal, magma-poor rift domain: example of the fossil Platta ophiolite, SE Switzerland - M.-E. Epin; G. Manatschal; M. Amman; C. Ribes; A. Clausse; T. Guffon; M. Lescanne (International Journal of Earth Sciences, 2019)

Trophic niche separation that facilitates co‐existence of high and low microbial abundance sponges is revealed by in situ study of carbon and nitrogen fluxes - T. Morganti; R. Coma; G. Yahel; M. Ribes (Limnology and Oceanography, 2017)
Sponges are commonly divided into high (HMA) and low (LMA) microbial‐abundance species according to the bacterial biomass in their tissue. These two groups reflect distinct aquiferous structures and feeding strategies. In the NW Mediterranean coralligenous community, HMA and LMA sponges are often packed in dense, multispecies assemblages that cover many pinnacles and overhangs. We investigated the metabolism of HMA and LMA species that cohabitate the coralligenous community by sampling in situ the inhaled and exhaled water. Sponges consumed plankton, dissolved organic carbon (DOC), and ammonium in relation to their abundance in ambient water. The plankton retention efficiency was high for all species. DOC was the main source of C for the sponge species, accounting for ∼ 90% of the examined sources. Nitrogen fluxes markedly differed between the two groups: plankton was the main source of nitrogen for LMAs that excreted dissolved organic nitrogen (DON) and ammonium. The nitrogenous waste products of LMAs were found to be the major source of nitrogen (up to 97%) for HMAs that efficiently removed DON and ammonium and excreted nitrate. The different capacity of both sponge strategies to use dissolved resources suggests a partial trophic niche separation related to HMA‐LMA dichotomy as a mechanism facilitating their dense co‐existence in the community. Our findings suggest that a mixed assemblage of sponges (and their associated microbes) is able to utilize the suspended particulate and dissolved material more efficiently than a single species population and may contribute to the understanding of the phenomena of the stability and diversity of dense sponge assemblages in oligotrophic habitats.

Spermiogenesis and biflagellate spermatozoon of the teleost fish Lampanyctus crocodilus (Myctophiformes, Myctophidae): ultrastructure and characterisation of its sperm basic nuclear proteins - E. Ribes; M. Cheema; R. González-Romero; D. Lloris; J. Ausió; N. Saperas (Cell and Tissue Research, 2015)

Sun Protection Among Spanish Beachgoers: Knowledge, Attitude and Behaviour - M. C. Cercato; V. Ramazzotti; I. Sperduti; A. Asensio-Pascual; I. Ribes; C. Guillén; E. Nagore (Journal of Cancer Education, 2015)

Specificity and temporal dynamics of complex bacteria–sponge symbiotic interactions - Johannes R. Björk; C. Díez-Vives; Rafel Coma; Marta Ribes; José M. Montoya (Ecology, 2013)
Microbes are known to form intricate and intimate relationships with most animal and plant taxa. Microbe–host symbiotic associations are poorly explored in comparison with other species interaction networks. The current paradigm on symbiosis research stems from species‐poor systems where pairwise and reciprocally specialized interactions between a single microbe and a single host that coevolve are the norm. These symbioses involving just a few species are fascinating in their own right, but more diverse and complex host‐associated microbial communities are increasingly found, with new emerging questions that require new paradigms and approaches. Here we adopt an intermediate complexity approach to study the specificity, phylogenetic community structure, and temporal variability of the subset of the most abundant bacteria associated with different sponge host species with diverse eco‐evolutionary characteristics. We do so by using a monthly resolved annual temporal series of host‐associated and free‐living bacteria. Bacteria are very abundant and diverse within marine sponges, and these symbiotic interactions are hypothesized to have a very ancient origin. We show that host–bacteria reciprocal specialization depends on the temporal scale and level of taxonomic aggregation considered. Sponge hosts with similar eco‐evolutionary characteristics (e.g., volume of tissue corresponding to microbes, water filtering rates, and microbial transmission type) have similar bacterial phylogenetic community structure when looking at interactions aggregated over time. In general, sponge hosts hypothesized to form more intricate relationships with bacteria show a remarkably persistent bacterial community over time. Other hosts, however, show a large turnover similar to that observed for free‐living bacterioplankton. Our study highlights the importance of exploring temporal variability in host–microbe interaction networks if we aim to determine how specific and persistent these poorly explored but extremely common interactions are.

Functional convergence of microbes associated with temperate marine sponges - M. Ribes; E. Jiménez; G. Yahel; P. López‐Sendino; B. Diez; R. Massana; J. H. Sharp; R. Coma (Environmental Microbiology, 2012)
Summary Most marine sponges establish a persistent association with a wide array of phylogenetically and physiologically diverse microbes. To date, the role of these symbiotic microbial communities in the metabolism and nutrient cycles of the sponge‐microbe consortium remains largely unknown. We identified and quantified the microbial communities associated with three common Mediterranean sponge species, Dysidea avara , Agelas oroides and Chondrosia reniformis ( Demospongiae ) that cohabitate coralligenous community. For each sponge we quantified the uptake and release of dissolved organic carbon (DOC) and nitrogen (DON), inorganic nitrogen and phosphate. Low microbial abundance and no evidence for DOC uptake or nitrification were found for D. avara . In contrast A. oroides and C. reniformis showed high microbial abundance (30% and 70% of their tissue occupied by microbes respectively) and both species exhibited high nitrification and high DOC and NH 4 + uptake. Surprisingly, these unique metabolic pathways were mediated in each sponge species by a different, and host specific, microbial community. The functional convergence of microbial consortia found in these two sympatric sponge species, suggest that these metabolic processes may be of special relevance to the success of the holobiont.

Can oceanic reanalyses be used to assess recent anthropogenic changes and low-frequency internal variability of upper ocean temperature? - L. Corre; L. Terray; M. Balmaseda; A. Ribes; A. Weaver (Climate Dynamics, 2012)

Efficacy of fosfomycin and its combination with linezolid, vancomycin and imipenem in an experimental peritonitis model caused by a Staphylococcus aureus strain with reduced susceptibility to vancomycin - M. E. Pachón-Ibáñez; S. Ribes; M. Á. Domínguez; R. Fernández; F. Tubau; J. Ariza; F. Gudiol; C. Cabellos (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

In vitro and in vivo activities of linezolid alone and combined with vancomycin and imipenem against Staphylococcus aureus with reduced susceptibility to glycopeptides - S. Ribes; M. E. Pachón-Ibáñez; M. A. Domínguez; R. Fernández; F. Tubau; J. Ariza; F. Gudiol; C. Cabellos (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Submarine Groundwater Discharge to the Coastal Environment of a Mediterranean Island (Majorca, Spain): Ecosystem and Biogeochemical Significance - Gotzon Basterretxea; Antonio Tovar-Sanchez; Aaron J. Beck; Pere Masqué; Henry J. Bokuniewicz; Ruth Coffey; Carlos M. Duarte; Jordi Garcia-Orellana; Esther Garcia-Solsona; Lorena Martinez-Ribes; Raquel Vaquer-Sunyer (Ecosystems, 2010)

Mass mortality in Northwestern Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2009)
Late in summer 2003, extensive mass mortality of at least 25 rocky benthic macro‐invertebrate species (mainly gorgonians and sponges) was observed in the entire Northwestern (NW) Mediterranean region, affecting several thousand kilometers of coastline. We were able to characterize the mortality event by studying six areas covering the main regions of the NW Mediterranean basin. The degree of impact on each study area was quantified at 49 sites by estimating the proportion of colonies affected in populations of several gorgonian species compared with reference data obtained in years without mortality signs. According to these data, the western areas (Catalan coast and Balearic Islands) were the least affected, while the central areas (Provence coast and Corsica‐Sardinia) showed a moderate impact. The northernmost and eastern areas (Gulf of Genoa and Gulf of Naples) displayed the highest impact, with almost 80% of gorgonian colonies affected. The heat wave of 2003 in Europe caused an anomalous warming of seawater, which reached the highest temperatures ever recorded in the studied regions, between 1 and 3 °C above the climatic values (mean and maximum). Because this exceptional warming was observed in the depth ranges most affected by the mortality, it seems likely that the 2003 anomalous temperature played a key role in the observed mortality event. A correlation analysis between temperature conditions and degree of impact seems to support this hypothesis. Under the present climate warming trend, new mass mortality events may occur in the near future, possibly driving a major biodiversity crisis in the Mediterranean Sea.

Mass mortality in NW Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2008)

Effects of water velocity on picoplankton uptake by coral reef communities - M. Ribes; M. J. Atkinson (Coral Reefs, 2007)

Fast ion conduction character and ionic phase-transitions in disordered crystals: the complex case of the minerals of the pearceite–polybasite group - L. Bindi; M. Evain; A. Pradel; S. Albert; M. Ribes; S. Menchetti (Physics and Chemistry of Minerals, 2006)

Temporal variability in zooplankton prey capture rate of the passive suspension feeder Leptogorgia sarmentosa (Cnidaria: Octocorallia), a case study - S. Rossi; M. Ribes; R. Coma; J.-M. Gili (Marine Biology, 2004)

Dietary fat intake and prostate cancer risk: a case–control study in Spain - Josep M. Ramon; Ricard Bou; Soledad Romea; M. Eugenia Alkiza; Merce Jacas; Josefa Ribes; Joaquim Oromi (Cancer Causes & Control, 2000)

Prey capture by a benthic coral reef hydrozoan - R. Coma; M. Ribes; C. Orejas; J.-M. Gili (Coral Reefs, 1999)

Retroviral properties inherent to viral erythrocytic infection in sea bass - R. M. Pintó; E. Ribes; J. Jofre; A. Bosch (Archives of Virology, 1995)